The impact of ECB policy on structural reforms - Malte Rieth; Jana Wittich (European Economic Review, 2020)
We estimate the impact of monetary policy on structural reform adoption in the euro area. We identify exogenous ECB policy changes through an event study that extracts the unexpected variation in euro area interest rates on policy announcement days. We find that surprise monetary expansions increase the number of reforms significantly and that the effect is stronger for countries with weaker macroeconomic fundamentals or tighter public budget constraints. These findings are consistent with the hypothesis that expansionary monetary policy, by attenuating the short-run costs of reforms and increasing governments' financial leeway, spurs competition-friendly supply-side policy.
Keywords: C23; E52; E58; P11; 330; Macroeconomic policy; Euro area; Event study; Panel data